Expert System for Monitoring Elderly Health Using the Certainty Factor Method - Marlinda, Linda; Widiyawati, Widiyawati; Widiastuti, Reni; Indrarti, Wahyu (Politeknik Ganesha Medan, 2020)
A person who is in the elderly phase will experience various decreases, ranging from decreased memory or senility, hormone production, skin elasticity, muscle mass, bone density, strength and function of body organs, and the immune system. As a result, it is difficult for the elderly or the elderly to fight against various kinds of disease-causing bacteria or viruses, comorbidities, and adaptation to the social environment. Due to the complexity of this health problem, improvements can not only be made in the aspect of health services but also improvements in the environment and engineering of population factors or hereditary factors, but it is necessary to pay attention to behavioral factors that have a considerable contribution to the emergence of health problems. This research uses the certainty factor (CF) method which can provide a measure of belief in a symptom as a measure of how much the value is in the later diagnosis. The purpose of making this expert system is so that patients, patient families, and medical teams can monitor the health of the elderly daily. The results of this study indicate that using the CF method has an accuracy rate of 91 percent for the prediction of patients who have cholesterol